Advancements in Sodium Alginate‐Based Colloidal Drug Delivery Systems: Bridging Research Into Clinical Practice - Ashutosh Gupta; Aniket Navale; Debadrita Ghosh; Parekh Nirmit Jigneshkumar; Kuljeet Kaur; Aditya Dev Rajora; Soji Soman; Sally A. EL‐Zahaby (Polymers for Advanced Technologies, 2026)
ABSTRACT Sodium alginate, an anionic polysaccharide obtained from brown algae and a versatile biomaterial for colloidal drug delivery systems. It has good biocompatibility, biodegradability, and mucoadhesive nature. Alginate has controlled and targeted drug delivery applications. This review discusses sodium alginate–based colloidal systems and presents fundamental research with potential for clinical translation. Alginate can undergo ionic crosslinking with divalent cations such as calcium with a wide range of delivery platforms, involving nanoparticles, hydrogels, vesicular carriers, nanoemulsions, and nanocomposites. These systems protect labile drugs, peptides, and proteins from degradation, increase bioavailability, and result in sustained or stimuli‐responsive drug release. This review highlights alginate with many colloidal carriers, such as liposomes, niosomes, transferosomes, exosomes, cubosomes, dendrimers, and quantum dots, to improve its stability, targeting efficiency, and therapeutic properties. Additionally, the fabrication techniques, thiolation increase mucoadhesion, permeability, and site‐specific delivery. Methods such as microfluidics, electrospinning, and 3D bioprinting show precise control over particle size and drug‐loading efficiency, supporting personalized drug delivery systems. Stimulus‐responsive alginate‐based systems are sensitive to pH, temperature, redox conditions, and light, indicating their ability to target cancer therapy, gastrointestinal delivery, wound healing, and tissue engineering. Furthermore, challenges remain, including variability in alginate composition, stability issues, limited doses of hydrophobic drugs, and a lack of large‐scale manufacturing and clinical studies.